Treatment-associated fatigue in cancer patients treated with immune checkpoint inhibitors: a systematic review and meta-analysis - Abdel-Rahman, Omar M.; Mehrabi, Arianeb (Clinical oncology, 2016)
Aims - Fatigue is one of the most prominent side-effects of immune checkpoint inhibition. Therefore, we assessed the risk of fatigue associated with inhibitors of the immune checkpoints. - Materials and methods - We examined data from the Medline and Google Scholar databases. We also examined original studies and review articles for cross-references. Eligible studies included randomised phase II and phase III trials of patients with cancer treated with ipilimumab, nivolumab, pembrolizumab and tremelimumab. The authors extracted relevant information on participants' characteristics, all-grade and high-grade fatigue and information on the methodology of the studies. - Results - In total, 17 trials were considered eligible for the meta-analysis. The odds ratio for all-grade fatigue for CTLA-4 inhibitors was 1.23 (95% confidence interval 1.07, 1.41; P = 0.003) and for high-grade fatigue was 1.72 (95% confidence interval 1.26, 2.33; P = 0.0005). Moreover, the odds ratio for all-grade fatigue for PD-1 inhibitors was 0.72 (95% confidence interval 0.62, 0.84; P < 0.0001) and for high-grade fatigue was 0.36 (95% confidence interval 0.23, 0.56; P < 0.00001). - Conclusions - The analysis of data showed that CTLA-4 inhibitors seem to be associated with a higher risk of all- and high-grade fatigue compared with control regimens, whereas PD-1 inhibitors seem to be associated with a lower risk of all- and high-grade fatigue compared with control regimens.